Harga Saham Syariah Ditinjau Dari Rasio Profitabilitas - Maharany, Indah Dewi; Ni'mah, Luthfiyatun (IAIN Kudus, 2021)
The results showed that EPS has a significant positive effect on Islamic stock prices. Based on the value of t count greater than t table (3.556> 1.67591), and based on the value of the significance coefficient of 0.001 which is smaller than 0.05. Dividend Per Share (DPS) has a significant positive effect on Islamic stock prices. Based on the value of t count greater than t table (1.833> 1.67591), and based on the value of the significance coefficient of 0.033 which is smaller than 0.05. Return On Assets (ROA) has a significant positive effect on Islamic stock prices. Based on the value of t count greater than t table (2.833> 1.67591), and based on the value of the significance coefficient of 0.049 which is smaller than 0.05. Return On Equity (ROE) has no effect on Islamic stock prices. Based on the t count value is smaller than t table (0.612 <1.67591), and based on the significance coefficient value of 0.543 which is greater than 0.05.